Use of authentic materials trough moodle platform to enhance the listening skill of students of Intermediate Intensive English i at the Department of Foreign Language of the University of el Salvador during the year 2014 - Carbajal Rivera, Jessica Liseth; López de Ascencio, Delvia Merab; Cruz Cubillas, Juan Carlos; Landaverde Castillo, Manuel Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2016)
Nowadays, technology plays an important role in education not only because it makes things easier to students and teachers, but also because it helps to develop and improve skills. This is essential for those who want to achieve a successful life in the future, by having a good job, and for those who want to overcome any professional challenges. Technology allows teachers to enhance their teaching skills and strategies, there is a free online learning management system which enables teachers to create their own online courses, it is called Moodle, Moodle is an educational tool and it can be used anytime, anywhere, as long as there is internet access available. Martin Dougiamas began his work on Moodle in 1998, today, more than 70,000 universities, corporations and schools, in over 200 countries and 100 languages, trust Moodle for their online learning,Moodle – Open source learning platform. Moodle.org. (n.d.). Retrieved July 24, 2014, from https://moodle.org/ The University of El Salvador is not an exception, the Foreign Language Department is using Moodle since 2010, as an extra resource for the language learning process. For foreign language students it is really important to enhance the language skills, in Moodle, students can develop and improve the four macro skills. The four macro skills are important to become English proficient students, however, the research is focused in listening skill, since a person who listens properly is able to react appropriately to a particular situation or towards a particular person.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanzas) -- Universidad de El Salvador, San Salvador, 2016.
Bibliografía : hojas 163-169
Audiencia general.